Third Five Year Plan Policy and Programme Government of Kerala - Planning Commission (Planning Commission, 1961)
General description.—Kerala State lies between 8°-15' and 12°-45' N. latitude and 74°-50' and 77°-30' E- longitude. The State is a long coastal strip between the Arabian Sea in the West and the Western Ghats in the East, with a width of not more than 75 miles at the broadest point in the middle and narrowing down to about 20 miles in the northern and southern extremities. It has a sea coast of about 360 miles on the Arabian Sea in the West.
Planning Department, Government of Kerala